Ayesha Abed Foundation : annual report 1997 - Ayesha Abed Foundation, BRAC (© BRAC, 2016)
1. Goals and services of AAF. 2. Management of AAF. 3. Description of activities. 4. Production process. 5. Cost structure. 6. Production bonus. 7. Financial report.